2013
DOI: 10.1111/chso.12034
|View full text |Cite
|
Sign up to set email alerts
|

‘Value’ing Children Differently? Migrant Children in Education

Abstract: This paper considers dilemmas around ‘value’ and the ‘valuing’ of children and childhood(s) in schools. I argue that in neo‐liberal contexts, processes of children's identity making become aligned with the idea of the corporate citizen – value and worth derived from the capacity to produce, excel, self‐regulate as well as consume in an ever expanding marketplace. Taking the positioning of migrant children as an exemplar, the paper explores the tensions in pedagogic practices between the valuing of migrant chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 28 publications
2
48
0
3
Order By: Relevance
“…These children also struggled to negotiate belongingness and decipher what was valued in their peer relationships. The study also found that some migrant children were very conscious of their behavior and strove to secure acceptance at school, most likely because of their feelings of vulnerability (Devine, ).…”
Section: Literature Reviewmentioning
confidence: 97%
“…These children also struggled to negotiate belongingness and decipher what was valued in their peer relationships. The study also found that some migrant children were very conscious of their behavior and strove to secure acceptance at school, most likely because of their feelings of vulnerability (Devine, ).…”
Section: Literature Reviewmentioning
confidence: 97%
“…In drawing upon in‐depth interviews with young Albanian migrants, he presents paper that unpacks their collective identifications and sense of belonging in relation to Greek society and their home country. In so doing, the paper contributes to a growing strand of literature on children's and young people's collective identities (Hengst, ), as these are mediated by migration, dislocation and transnational mobility (Anthias, ; Bailey, ; Colombo and others, ; Devine, ; Fangen, ; Fassetta, ; Ní Laoire and others, ; Valentine and others, ).…”
Section: Introductionmentioning
confidence: 94%
“…For educational organisations, the limitation of risk offered by institutional distrust frees resources for the attainment of curricular goals via the exclusion of categories of students. In educational situations, categorical distinctions stabilise social relationships, but also positions of marginalisation (with regard to migrant students, see Devine 2013). Institutional trust and institutional distrust may be understood as consequences of the operations through which educational organisation reproduce themselves.…”
Section: Modena Intendiamoci December 2006mentioning
confidence: 99%